Urbanization processes along the Mediterranean coast of Alicante province. - Pablo Marti; Almudena Nolasco (European Regional Science Association (ERSA), 2011)
The rate of land consumption in the coastal area of Alicante has been over the last decades, one of the highest among all Spanish Mediterranean provinces. This new territorial tendency has involved important changes in the use of land and has led to a new spatial and functional reality. The objective of this paper is to address two specific concerns related to the identification and characterization of these recent artificial surfaces, focusing on the assessment of quantitative details (land consumption surface, density, population, etc.) and qualitative features (morphologies, landscape impact, etc.). The methodological approach is based on graphic and statistical analysis. On the one hand, starting by first identifying artificial areas by comparing satellite imagery (source: the European project Corine Land Cover - 1990, 2000 and 2006). It is possible then, to study in detail the new developments thanks to the aerial photographs (1993, 2002 and 2008). On the other hand, the variety of statistical databases -local, regional and state statistics such as census, registers and other government studies- make possible to quantify and qualify the details of these new urban areas. Thus, the foreseen results are related to the characterization and definition of new urban patterns along the coast of Alicante, taking in account that the identification of the new patterns of urban and territorial occupancy is an important clue in order to establish future planning in both local and regional level.
Keywords: 330